Transfer Pemerintah Pusat dan Pertumbuhan Ekonomi di Provinsi Papua Barat (Granger Causality Approach) - Lillyani Margaretha Orisu (EKO-REGIONAL, 2012)
This study focus to analysis and evaluate the causality of central government transfer fund and economic growth in the region of West Papua Province. Using secondary data from BPS, Bappeda and BKPMD. Estimation method that used in this research is Granger Causality test.Results showed that central government transfer fund at the fisrt time lag in the model significantly affecting economic growth, at the fourth lag there is a bilateral causality between central government transfer fund and economic growth significantly affecting each other. Keywords:   central government transfer fund, economic growth